Industrialisation and the big push in a global economy - Udo Kreickemeier; Jens Wrona (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
In this paper, we develop a multi-country open economy extension of the famous Big Push model for a closed economy by Murphy et al. (1989). We show under which conditions the global economy in our model is caught in a poverty trap, characterised by a low-income equilibrium from which an escape is possible (only) via a coordinated modernization effort across sectors and countries. We also analyze to what extent the degree of openness matters for the prospects of achieving the high-income equilibrium. We show that under monopolistic competition with CES preferences the openness to international trade does not affect the set of parameter combinations leading to a poverty trap, whereas international trade makes it more difficult to achieve industrialisation through a Big Push with continuum quadratic preferences. Responsible for this adverse outcome is the pro-competitive effect of opening up to international trade, which bites into firms' profit margins, rendering the adoption of a superior production technology unprofitable as it becomes more difficult for firms to amortise their adoption fixed costs.
Keywords: F12; O14; F43; 330; Big Push; multiple equilibria; backward linkages; international trade; globalisation; poverty trap; technology upgrading; monopolistic competition